Exploring Tourists' Knowledge, Perceptions and Willingness to Pay on Biodiversity Conservation: Insights from Kinabalu Park, Borneo - Fazilah Musa; N S Ahmad Nasir; O Jaunis; D D Mohd Hamdan (2021)
The richness of biodiversity and ecotourism development in Malaysia has contributed to economic growth and human well-being. In this context, Kinabalu Park, Borneo, offers the uniqueness of biodiversity as the main attraction to local and foreign tourists. However, the economic value of biodiversity is difficult to quantify due to the non-existent market for these resources. This study explored the tourists' knowledge and perception regarding the biodiversity issues and estimated the Willingness to Pay (WTP) for Kinabalu Park's biodiversity conservation using the Contingent Valuation Method (CVM). A total of 250 questionnaires with five bid prices were distributed to local (RM3, RM6, RM9, RM12, and RM15) and international tourists (RM15, RM30, RM45, RM60, and RM75). This study reported that more than half of the respondents are willing to pay for the conservation of biodiversity. Most local and international tourists are willing to pay RM5 and RM84.05 per person, respectively. The Principal Component Analysis (PCA) in Factor Analysis showed that the "environmental" factor had the highest eigenvalue compared to the "social" factor. This finding shows that tourism has a very significant environmental attitude and preferences towards the conservation of biodiversity. The financial planning management can help the stakeholders in biodiversity conservation programs at Kinabalu Park for better governance in the future.